Perceptions and attitudes toward blue energy and technologies in the Mediterranean area: ASKYOURCITIZENSONBE - Betti, Gianni; Cervellera, Gian Piero; Gagliardi, Francesca; Gioia, Carmela; Patrizi, Nicoletta; Bastianoni, Simone (Frontiers in Energy Research, 2022)
An energy transition is needed in order to meet the European pledge of reaching climate neutrality by 2050. This transition cannot ignore the renewable resources available from 70% of the Earth (namely, the oceans and seas). This concept is fundamental for the planet and especially important for the Mediterranean area. Marine renewable energies are still under-deployed in the Mediterranean area for many reasons, including legislative constraints, lower energy availability and technological readiness. An appropriate participatory process including all actors (e.g. policy makers, firms, citizens, researchers) is necessary for a correct path towards decarbonization. The BLUE DEAL project was conceived and implemented by 12 Mediterranean partners to tackle these issues and set the route for blue energy deployment in the Mediterranean area. Activities already conducted include a survey to probe the perceptions and attitudes of citizens towards blue energy. The survey targeted about 3000 persons in 12 Mediterranean sites with the aim of bringing citizens into the discussion on future technologies. The results showed that although blue energy is still relatively unknown to the general public (only 42% of respondents were aware of these technologies), there was a general willingness (70%) to host one or more such installations in their areas. Here we describe our survey method and some empirical results with suggestions for replicability and recommendations on how to use it for policymaking purposes.